PENERAPAN ENTERPRISE RESOURCE PLANNING SYSTEM PADA PT GARUDA INDONESIA (PERSERO) - Kurniawati, Elisabeth Penti; Eka Permadi, FX Rahardian (Jurnal Manajemen dan Keuangan, 2011)
Information technology gives more support in achieving companyâs objectives, esspecially for companies who rely on high information technology. Information technology supports companyâs information system in processing data in order to become reliable information. Therefore, company management should maintain their information reliability. The implementation of Enterprise Resource Planning system (ERP system) can help company management in maintaining information reliability. The aim of this research is assessing the implementation of Enterprise Resource Planning system (ERP system) at PT Garuda Indonesia (Persero). The arrangement of the research is how PT Garuda Indonesia (Persero) runs the preparation of ERP systemâs implementation and the ERP systemâs implementation. This research is done at PT Garuda Indonesia (Persero) information system division. The analysis technique applied in this research is qualitative analysis using descriptive method. Generally, it can be conclude that PT Garuda Indonesia (Persero) has successfully runs the preparation of ERP systemâs implementation and so does with the ERP systemâs implementation.Keywords: information system, information technology, Enterprise Resource Planning system (ERP system)